Analisis Sirkumstan dalam Teks Terjemahan dengan Pendekatan Sistemic Functional Linguistics (SFL) - Irawati; Gusnawaty; Tadjuddin Maknun; Muhammad Hasyim; Asriani Abbas (Universitas Cokroaminoto Palopo, 2022)
This research is a descriptive research. In this study, researchers analyzed the circumstantial elements contained in a children's story book entitled The 7 Habits of Happy Kids by Sean Covey and its translation. The approach used in this research is Systemic Functional Linguistic (SFL). The method used in this study is the results showed that the types of circumtances that appear in the bilingual children's story book are 7 types of circumtances consisting of: location, extension, role, matter, manner, accompaniment and cause circumtances. The seven circumstantials are formed by words, groups of words and prepositional phrases. These forms can be grouped into: (1) accompaniment circumstantial formed by prepositional phrases, (2) circumstantial ways include 4 types, namely tools, quality, comparison and degree. The method circumstantial (tool and comparison) is formed by prepositional phrases and word groups while the manner (quality and degree) circumstantial is formed by words and word groups, (3) the location circumstantial includes 3 types, namely time, place and space. Time and place circumstantials are formed by words, groups of words and prepositional phrases while space circumstantials are only formed by prepositional phrases, (4) role circumstantials are formed by prepositional phrases and word groups, (5) external circumstantials are formed by words, groups of words and prepositional phrases, (6) circumstantial matter is formed by prepositional phrases, and (7) circumstantial cause includes 3 types, namely behalf, purpose and reason. The three types of circumstantial cause are only formed by prepositional phrases. Children's stories in the books studied are dominated by circumstantial time and place locations. Keywords: transivity, circumtances, translated text